The role of digital media in shaping youth planetary health interests in the global economy - Ibrahim Niankara; Muhammad Noor Al adwan; Aminata Niankara (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Despite revolutionizing the work of practicing economists by providing a direct link between neo-classical economic theory and revealed market preference data, Random Utility Theory has yet to guide research applications in global market sustainability. With the worldwide adverse socio-economic effects of the 2019 coronavirus disease (COVID-19), such application now becomes timely. Therefore, relying on a Random Utility theoretic formulation of youths' preferences for the biosphere (ecosystem services, sustainability) and science-based disease prevention to characterize their planetary health interests, this paper adopts a micro-based planetary view of markets to retrospectively analyze the health and ecological implications of digital media consumption among youths in the global economy. Empirically, we rely on a mixed bivariate ordered probit specification, which is estimated using Markov Chain Monte Carlo methods. Our findings reveal a strong, positive correlation coefficient (0.835) between youths' interests in the biosphere and science-based disease prevention. Moreover, digital media consumption in the form of increased frequency of ecological website visits, news blogs visits, and web-browsing on broad science, significantly reduce youths' interests in the biosphere. A similar reduction in youths' interest in science-based disease prevention is observed, from news blogs visits and web-browsing on broad science. Conversely, ecological website visits appear to raise youths' interests in science-based disease prevention. Furthermore, we find a gender-based gradient in youths' planetary health interest, in favor of the female gender. Overall, our findings confirm the appropriateness of a holistic view of health, and suggests a couple of policy implications for the long-term sustainability of our planet.
Keywords: 650; adolescents health; bayesian methods; COVID-19; digital media; ecosystem services; planetary health; sustainable development